Numerical study on materials with micro-structures - Cheng, Xin Wei (Nanyang Technological University, 2020)
Composite materials have a versatile feature over conventional materials such as steel, aluminum or wood. The properties of composites such as high strength to weight ratio, high stiffness or high strength make it an attractive option for various usage. A category of composites, the bi-continuous composites, are composites that have an interpenetrating and continuous phases matrix and dispersed phase. Due to its internal microstructure, a bi-continuous composite exhibit improved properties over the conventional composites and is used for a wide range of applications in the industry. However, the research development of the bi-continuous composite has been slow due to its complex and random microstructure. The aim of this project is to investigate the effects of the number of interfacial cracks on the elastic properties of an Aluminium-Alumina bi-continuous composite. An additional aim of this project is to investigate the effects of the interfacial cracks’ orientation on the elastic properties of an Aluminium-Alumina bi-continuous composite. To conduct the investigation, a model was created using a finite element model and was simulated on ANSYS APDL. As anticipated, the results have shown that the addition of cracks would weaken the composite, reducing its elastic modulus. However, when the concentration of Aluminum is higher than Alumina, there was a reduction in the crack’s weakening effects. Thus, it had caused the bi-continuous composite’s elastic modulus to fall within a specific range. In the investigation on the cracks’ orientation, the results have shown that the bi-continuous composite was stronger when the cracks are not aligned perpendicular to the tensile stress. However, there was a huge variation on the results which might suggest several computational errors during the simulation. Therefore, further studies and optimisation are required on the method of analysing the effect of the cracks’ orientation on the bi-continuous composite.